The systematic approach to solving the problem of personnel training based on use of 8D methodologies - L. G. Varepo; L. V. Boyarnikova; E. V. Leongardt (Омский научный вестник)
The article discusses the procedure for managing inconsistencies using the example of the «personnel training» element, which is part of the «resource management» process using the 8D methodology. The case of identifying the root cause of the problem arising during distance learning for employees of closed-type enterprises has been analyzed, corrective and preventive actions have been developed. The calculation of the performance assessment was carried out and the report form was compiled according to the 8D methodology.